EFEKTIFITAS RELAKSASI BENSON TERHADAP PENURUNAN INTENSITAS NYERI LUKA POST SEKSIO SESARIA - Ade Sarah Sinta Dewi (Coping: Community of Publishing in Nursing, 2015)
Benson Relaxation is the development of a response relaxation method by involving patient belief factor to relieve post operative pain. It focuses on certain word or sentense pronounted many time in a regular breath rythm according patient belief. This research was aimed to explore Effectiveness of Benson Relaxation to decrease post caesarean sectio wound pain intensity in Bakung Timur Room at Sanglah Hospital. The method used in this study was quasi experimental design using pre test and post test design with control group. The sample consisted of 30 participants post caesarean sectio selected by purposive sampling techniques, devided into two groups, namely intevention and control group, is participants respectively. In the intervention groups given Benson Relaxation combined with analgesic therapy and control gruops just given analgesic therapy. The pain intensity of pre test and post test for both groups, pain scale was measured by using Visual Analog Scale (VAS). The results revealed that combination Benson Relaxation and analgesic therapy was more analgesic alone with Sig.(2 tailed) of 0,023 (p<0,05). Which means significant Benson Relaxation to decrease post caesarean sectio wound pain intensity in Bakung Timur Room at Sanglah Hospital.